Engaging employees for success: Enhancing generational performance and closing generational divide / Lee Su Teng - Lee, Su Teng (2013)

(untitled)
The primary aim of this research is to examine the generational differences in the engagement model. The study set out to examine the mediating influence of employee engagement in the relations between motivators and consequences, and whether this relationship is moderated by generations. This study consists of two phases. Phase 1 was a one-to-one interview of 63 participants while phase 2 was a survey study of 539 respondents. The unit of analysis is individuals who represent Malaysian employees from different organisations in Peninsular Malaysia. This study is backed by well-established theory from social psychology, the social exchange theory. IBM Statistical Package for Social Sciences (SPSS) Statistics 20 was used to perform exploratory factor analysis (EFA), reliability tests and preliminary correlation analysis. In addition, IBM SPSS Analysis of Moment Structures (Amos) 18 was used to test the hypotheses of the study. Findings show that there are generational differences in the Malaysia context. There are significant local historical events, work values, expectations, perceptions, behaviours, goal, leadership style and motivators for each generation. Results also show that each generation reacts differently to the motivators of employee engagement. To engage Boomers, employers should focus on reward and recognition from the immediate supervisor and colleague, as well as autonomy. For the engagement of Generation X, leaders can consider implementing work-life balance programme, autonomy as well as reward and recognition from the Management. In order to engage Generation Y, what they want is just reward and recognition from the immediate supervisor and colleague, as well as work-life balance. It was found that engaged employees from Generation X and Y have lower intention to leave, increased in-role performance and innovative job performance. However, engaged Boomers only displayed increased in-role performance. All these v lead to finding new and more harmonious ways of establishing working relationships and engaging the employees for all generations.